Recalculation of Pump Speed and Stroke Length to Increase Production Rate and Volumetric Efficiency of HPU Well BTN-01 - Indarti, Adrian; Fitri, Muhamad Bintang (Gema Wiralodra, 2024)
In the "BTN-01" well, one of the wells is owned by KSO PT PERTAMINA EP PT Sarana GSS Trembul. The "BTN-01" well is installed with a hydraulic pumping unit pump that experiences decreasing production, and based on tests on January 30, 2023, the output of the "BTN-01" well produces only 216 bfpd with 98% of water cut. The pump operates on 8 SPM of pump speed and 74-inch stroke length, with 43% of volumetric efficiency. As per theory, a proper design of hydraulic pumping unit pump will produce a volumetric efficiency value above 70%. To overcome this problem, it is necessary to perform research, started with an evaluation on the existing design and continue to quantitative research by recalculating the optimum production rate from IPR calculation, recalculating pump speed, recalculating pump stroke length, and recalculating volumetric efficiency to achieve higher value on both production rate and volumetric efficiency of the pump. In the "BTN-01" well, IPR was calculated by the Wiggins method, and it is known that the oil production rate is 5.53 bopd, 421.96 bwpd of water rate, and the fluid production rate is 427.5 bfpd. Based on the results of HPU redesign and recalculation of the optimum production rate, the new value of pump speed is 7 SPM (existing 8 SPM), the pump stroke length is 70 inches (existing 74 inches) with a volumetric efficiency of 78.45% (existing 43%) that can be called optimal.